The boy in the striped pajamas : a fable - Boyne, John, 1971- (Oxford ; New York : David Fickling Books, 2006)
Bored and lonely after his family moves from Berlin to a place called "Out-With" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.
"Berlin 1942. When Bruno returns home from school one day, he discovers that his belongings are being packed in crates. His father has received a promotion and the family must move from their home to a new house far far away, where there is no one to play with and nothing to do. A tall fence running alongside stretches as far as the eye can see and cuts him off from the strange people he can see in the distance. But Bruno longs to be an explorer and decides that there must be more to this desolate new place than meets the eye. While exploring his new environment, he meets another boy whose life and circumstances are very different to his own, and their meeting results in a friendship that has devastating consequences." -- Publisher's website.
Accelerated Reader/Renaissance Learning
AR
Accelerated Reader
Reading Counts
Accelerated Reader AR
Keywords: Auschwitz (Concentration camp) -- Juvenile fiction; Fables; Jugendbuch; Historical fiction -- Young adult; YRCA book award: Junior: Winner -- 2009.; Fiction; Juvenile works; Young adult fiction; 1080L.; Fables; Juvenile fiction